Comparison of SRK/T with Kane formula for prediction of refractive outcome after phacoemulsification: Insights from a South Asian patient group - Sana Nadeem (Elsevier, 2024)
Background: Phacoemulsification stands as the most commonly conducted ocular procedure. Biometry represents an art with numerous generations of formulas introduced to enhance refractive prediction accuracy. The Sanders Retzlaff Kraff theoretical (SRK/T), a third-generation formula that merges linear regression and a theoretical eye model, and the Kane formula, a fourth-generation formula incorporating theoretical optics, regression, and artificial intelligence, embody our focal points. Our aim is to compare post-operative refractive outcomes utilizing SRK/T and Kane formulae for calculating intraocular lens (IOL) power in senile cataract patients undergoing phacoemulsification featuring a hydrophilic acrylic, monofocal IOL. Methods: This prospective, interventional institutional study engaged 70 patients, totaling 74 eyes. They were categorized into two groups: Group A employed the SRK/T for IOL power calculation, while Group B used the Kane formula. Quantel Medical® A-scan biometer was employed. A comparison was drawn between both formulae in terms of mean absolute error (MAE) and median absolute error (MedAE), with the utilization of IBM SPSS 20 and a significance level of p < 0.05. Results: The MAE for the SRK/T and Kane formulae stood at 0.18 ± 0.82 D and 0.24 ± 0.94 D, respectively, while the MedAE recorded values of 0.16 D and 0.155 D, correspondingly (p < 0.05). Conclusion: Within this South Asian cohort of senile cataract patients, the SRK/T formula demonstrated a marginally improved refractive outcome, evidenced by a reduced mean absolute error.